1993
DOI: 10.1016/0014-5793(93)80945-q
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the disulphide bridge arrangement of bovine histidine‐rich glycoprotein

Abstract: Histidine‐rich glycoprotein (HRG) was purified from bovine plasma and the disulphide bridge arrangement established. Disulphide‐bridged peptides were obtained from peptic and tryptic degradation of native bovine HRG. Twelve half‐cystine residues were found in bovine HRG (compared to sixteen cysteines in human HRG), all involved in the formation of six disulphide bridges connecting Cys‐1 to Cys‐12, Cys‐2 to Cys‐3, Cys‐4 to Cys‐5, Cys‐6 to Cys‐11, Cys‐7 to Cys‐8, and Cys‐9 to Cys‐10. Additional sequence analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Based on the experimental detection of the disulfide bridges, it has been determined that the 12 cysteine residues of bovine HPRG form 6 disulfide bonds [31]. Genome sequence data indicate that also rabbit HPRG contains 12 cysteine residues.…”
Section: Disulfide Bridges Arrangement In Hprgmentioning
confidence: 99%
“…Based on the experimental detection of the disulfide bridges, it has been determined that the 12 cysteine residues of bovine HPRG form 6 disulfide bonds [31]. Genome sequence data indicate that also rabbit HPRG contains 12 cysteine residues.…”
Section: Disulfide Bridges Arrangement In Hprgmentioning
confidence: 99%
“…The other interdomain disulfide is unique to HRG and connects the N2 domain to a linker region between the HRR and PRR2 domains (Figure 1). 28 A peptide corresponding to the HRR/ PRR fragment has been identified in human tissue samples but the mechanism by which the interdomain disulfide is reduced is not known. 29 Using x-ray crystallography we present the first structural characterization of HRG.…”
Section: Introductionmentioning
confidence: 99%
“…Although HRG has been classified as a member of the cystatin supergene-family that are generally known as cysteine protease inhibitors, 9 no protease inhibitory activity has been reported for HRG. HRG also contains 4 intradomain and 2 interdomain disulfide bridges, 10 and 6 predicted N-linked glycosylation sites. 2,5 The protein and gene structure of HRG have been reviewed in detail by Jones et al 3 A variety of molecules have been shown to interact with HRG, including heme, 11 Zn 2ϩ , 12 plasminogen, 13 heparanase, 14 fibrinogen, 15 thrombospondin (TSP), 16 vasculostatin, 17 immunoglobulin G (IgG), 18 complement components, 18,19 and heparin.…”
Section: Introductionmentioning
confidence: 99%